The first-ever reported primary spinal infection with Aeromonas (Indian Journal of Case Reports, 2024)
Back pain can be an insignificant symptom in most patients in the intensive care unit. However, a simple complaint of back pain can have a tell-tale behind it. We present the case of a 57-year-old patient who presented to us with thrombocytopenia, leukocytosis, and urinary symptoms. Investigating her back pain revealed that she had a spinal epidural abscess with a very rare organism like Aeromonas hydrophila with no risk factors for the same. She had no prior history of trauma or any spinal surgeries. Hence, this is a primary Aeromonas spinal infection with no other source of seeding from any other sites. Our understanding and review of the literature could not find us any other case reports ever reported.